Estudios sobre el género Inocybe (Agaricales) en la Península Ibérica e Islas Baleares, V. Inocybe squarrosa var. macrosperma var. nov., descubierto en Cataluña - Esteve-Raventós, Fernando; Tabarés Carriedo, Manuel (Revista Catalana de Micologia, 2007)
Studies on the genus lnocybe (Agaricales) in the Iberian Peninsula and Balearic Islands, V. Inocybe squarrosa var. macrosperma var. nov., discovered in Catalonia. I. Squarrosa var. macrospenna var. nov. is described; a historical survey of this rare species is made. Line drawings of its microcharacters are given.